Centralization and the capitalist market economy - Kornai, János (Journal of Public Governance, 2012)
According to the author, a radical change has occurred in the political structure of the Hungarian state: it is not a democracy any more, but an autocracy. In close relation to this, the article views the damage done to societal and state institutions. The author does not call for any changes of emphasis – he is still convinced that the main problem lies in the replacement of democracy by autocracy – but he views his previous conclusions from a different angle: the tendency to centralize. The author claims that in most countries, the state and the capitalist market economy coexist in some way. In fact, the relation can be very benefi cial in some cases, despite frictions. On the one hand, state intervention cushions the market’s failures and makes income distribution fairer. On the other, the market flexibly and effectively corrects the government’s mistakes. But these fortunate cases do not refute the general observation that state and market are two different kinds of organism, alien to each other: their coexistence is not easy.Over the last two years, the Hungarian government’s measures have alternated between elements of socialism and capitalism, centralization and decentralization, and state and market activity. As a result, the Hungarian modus operandi fails to profit from the capitalist system: the propensity for innovation, dynamism, initiative and a spirit of enterprise. At the same time it brings out all the drawbacks inherent in capitalism. The government and the market work together to make the income distribution still more unjust; they operate side by side to produce and sustain mass unemployment.